GROUND IMPROVEMENT OF A COAL ASH STORAGE POND USING SAND COMPACTION PILES - S. S. Lin; C. J. Chien; J. C. Liao (Lowland Technology International, 2008)
Effects of sand compaction piles on ground improvement of a coal ash pond and axial performance on four drilled shafts through improved coal ash layer at a power plant in southern Taiwan is studied in this paper. Effects of the sand compaction piles improvement is evaluated by comparing the SPT-N values before and after ground improvement. The load versus displacement relation at head, the axial force along the shaft, the t-z curves and/or the toe q-z curve, which are the main concerns of shaft load test results, are presented and discussed in the paper. Applicability of the β value used by O’Neill and Reese (1999) for estimating shaft skin friction resistance of soil with no cohesion through improved coal ash layer is evaluated by comparing to the test measured results.